2019
DOI: 10.1183/13993003.02445-2018
|View full text |Cite
|
Sign up to set email alerts
|

Riociguat for treatment of pulmonary hypertension in COPD: a translational study

Abstract: Chronic obstructive pulmonary disease (COPD), which comprises the phenotypes of chronic bronchitis and emphysema, is often associated with pulmonary hypertension (PH). However, currently, no approved therapy exists for PH-COPD. Signalling of the nitric oxide (NO)–cyclic guanosine monophosphate (cGMP) axis plays an important role in PH and COPD.We investigated the treatment effect of riociguat, which promotes the NO–cGMP pathway, in the mouse model of smoke-induced PH and emphysema in a curative approach, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…on RV stroke volume, assessed by MRI, at rest or during exercise (Rietema et al, 2008). More recently, an open‐label study also showed that riociguat, an sGC stimulator, improved PVR (Pichl et al, 2019).…”
Section: Clinical Studies/treatment Of Copd–ph In Humansmentioning
confidence: 98%
See 1 more Smart Citation
“…on RV stroke volume, assessed by MRI, at rest or during exercise (Rietema et al, 2008). More recently, an open‐label study also showed that riociguat, an sGC stimulator, improved PVR (Pichl et al, 2019).…”
Section: Clinical Studies/treatment Of Copd–ph In Humansmentioning
confidence: 98%
“…Similarly, stimulation of sGC by BAY 41‐2272 in tobacco smoke‐exposed guinea pigs reduced PVR and vascular remodelling and prevented emphysema development (Weissmann et al, 2014). In a recently published study, riociguat was also shown to be effective in reversing fully established emphysema and decreasing RVSP, muscularization of small pulmonary vessels, and RH hypertrophy in smoke‐exposed mice and had beneficial effects on PH without disturbing oxygenation in a, however, small cohort of COPD patients (Pichl et al, 2019). For the potential downstream signalling events mediating therapeutic effects of sGC stimulation on parenchymal integrity, the authors propose down‐regulation of MMPs and inducible NOS (iNOS) and up‐regulation of FGF10 expression.…”
Section: Pharmacological Therapies For Ph In Animal Models Of Copdmentioning
confidence: 99%
“…Other drugs used for pulmonary hypertension, such as sildenafil and riociguat, might have a role in modulation of pulmonary perfusion during OLV. However, application of these drugs during anesthesia is challenging [23].…”
Section: Discussionmentioning
confidence: 99%
“…After 10 minutes of fixation, the lung has been removed and kept in formalin solution for 24 hours, followed by dehydration and paraffin embedding. This method prevents atelectasis formation and ensures constant airway pressure during fixation of the lung structure for further quantification by standard morphometric assessment of the mean linear intercept (MLI) that is established in our group (24).…”
mentioning
confidence: 99%
“…In a mouse model of cigarette smoke–induced emphysema that is established in our laboratory, we observed a similar degree of emphysema. A long-term exposure of 8 months leads to development of emphysema, seen as a 15–30% increase in MLI (2, 4). It appears that in rodent models, because of the significantly shorter life span, symptoms of chronic diseases such as emphysema do not reach severity as observed in human patients.…”
mentioning
confidence: 99%